Antibacterial Activities of Ethanolic Extract Obtained from Rhododendron myrtifolium Schott & Kotschy Leaves Against Clinically Isolated Bacterial Strains - Honcharenko, Vitaliy; Tkachenko, Halyna; Prokopiv, Andriy; Nachychko, Viktor; Sosnovsky, Yevhen; Góralczyk, Anna; Osadowski, Zbigniew (Agrobiodiversity for Improving Nutrition, Health and Life Quality, 2019)
The plants belonging to the genus Rhododendron L. and isolated compounds demonstrate diverse biological activities including anti-inflammatory, analgesic, anti-microbial, anti-diabetic, insecticidal and cytotoxic activity, as well as antibacterial activity. Our study was designed the effects of Rhododendron myrtifolium Schott & Kotschy leaf extract against bacterial strains were monitored in vitro by the disk diffusion method. The aim of this study was to assess possible antibacterial effects of an ethanolic extract derived from Rhododendron myrtifolium leaves against Citrobacter freundii, Enterobacter cloacae, Klebsiella pneumoniae, and Escherichia coli strain locally isolated from human biological fluids. Thus, the study contributes to on-going investigations on the bioactivity potential of plant species such as the Rhododendron. Leaves of Rhododendron myrtifolium were harvested on the side of the road between the Menchul valley and Rogneska valley (Kvasy village, Rakhiv district, Zakarpattia region, Ukraine). The results revealed that extract exerts antibacterial activity against Citrobacter freundii. However, the Enterobacter cloacae, Klebsiella pneumoniae, and Escherichia coli were resistant to R. myrtifolium leaf extract. Maximum in vitro inhibition was scored against Citrobacter freundii, followed by Escherichia coli, Klebsiella pneumoniae, and Enterobacter cloacae, which presented inhibition zones of (12.1 ±0.9) mm, (9.1 ±0.5) mm, (7.5 ±0.6) mm, and (7.2 ±0.5) mm, respectively. In the case of the positive controls, 96 % ethanol possesses a mild antibacterial effect, which presented inhibition zones of (6.5 ±0.7) mm. The results from the screening study performed by the disc diffusion method revealed that R. myrtifolium possesses a mild antibacterial activity against C. freundii. However, further investigation is needed to determine the bioavailability of the active compounds and to determine the dose and toxicity before it can be used as therapeutic agents.